Mycobacterium bovis tuberculosis in a neonatal holstein calf - Mehmet Burak Ateş; Mustafa Kemal Çiftçi; Ertan Oruç; Ayşe Çelebi; Gökhan Akçakavak (Eurasian Journal of Veterinary Sciences)
In this study, a case of exudative type tuberculosis due to M. bovis infection was identified in a 2 month-old Holstein female calf that was treated with antibiotic treatment due to cough and respiratory problems in the neonatal period. Systemic necropsy revealed caseific nodules scattered across the entire lung, except the dorsal parts of the caudal lobes of the lung, and prominent interlobular edema was observed in the dorsal caudal regions. Histopathologically, exudative lesions that extensive caseification necrosis and calcification with diffuse inflammatory cells and Langhans type giant cells without fibrous capsule were seen in the lung parenchyma. Smaller and lesser number of similar granulomas was found in the liver and brain. Acid resistant bacteria in Ziehl-Neelsen staining were determined to be Mycobacterium bovis in immunohistochemical staining. It is aimed to draw attention to the fact that bovine tuberculosis should be considered as one of the important diseases affecting the calves in the neonatal period and may cause serious economic losses if no measures are taken.